The Communicative Role of Contract-Based Archivists in Optimizing Archival Governance at IAIN Kudus - Triana Ratnasari; Priyo Wicaksono (JURNAL DIGITAL MEDIA, CULTURE, AND HUMANITIES, 2025)
IAIN Kudus, as one of the State Islamic Higher Education Institutions (PTKN) in Indonesia, plays a significant role in the advancement of science and Islamic studies. In performing its duties and functions, IAIN Kudus comprises various units, centers, faculties, and institutions. By strengthening the Central File Function and the Record Center II Function through the role of Contract-Based Archivists (P3K), the institution can improve operational efficiency, reduce the risk of losing essential information, and ensure compliance with archival management regulations. This study aims to explore the strategic role of P3K Archivists as information and document managers, enhancing the efficiency and effectiveness of institutional archival governance. Using a descriptive qualitative method, this study focuses on the Central File and Record Center II Functions as stipulated in Rector’s Regulation, along with archival human resources at IAIN Kudus. Data collection was conducted through observation and literature review of relevant journal articles. The results demonstrate that the role of P3K Archivists in supporting the Central File Function and Record Center II Function at IAIN Kudus can be optimized to strengthen institutional archival governance.